Second Culture, Good Vibrations, and Writings on the Wall: Hip-Hop in the GDR as a Case of Afro-Americanophilia - Leonard Schmieding (PORTAL: Journal of Multidisciplinary International Studies, 2015)
This essay examines Afro-Americanophilia in the German Democratic Republic by analyzing the cultural transfer of hip-hop between 1983 and 1990. It argues that the individuals who participated in this transfer from the United States into East Germany shared an appreciation of African Americans and Black culture and thus facilitated the import, growth, and dissemination of breakdance, graffiti, rap, and deejaying. Focusing on three individuals, it details the specific characteristics of their Afro-Americanophilia and scrutinizes their roles for the hip-hop scene in state socialism. While a cultural critic interpreted hip-hop as ‘second culture,’ which, according to Marxist-Leninist ideology, was to be endorsed as international working-class culture, a radio host from East Berlin spread information and music throughout the country, equipping the teenage audience with what they needed for their own practice of hip-hop. Finally, a look at a graffiti writer from Dresden shows how hip-hop artists imagined themselves into the community of hip-hop in New York City and fashioned themselves as Black youth living in the Bronx.